Modelling the effects of stocking rate, soil type, agroclimate location and nitrogen input on the grass DM yield and forage self-sufficiency of Irish grass-based dairy production systems. (8th June 2022) - Ruelle, E.; Delaby, L.; Shalloo, L.; O'Donovan, M.; Hennessy, D.; Egan, M.; Horan, B.; Dillon, P.
Abstract: In pasture-based dairy production systems, identifying the appropriate stocking rate (SR; cows/ha) based on the farm grass growth is a key strategic decision for driving the overall farm business. This paper investigates a number of scenarios examining the effects of SR (2–3 cows/ha (0.25 unit changes)), annual nitrogen (N) fertilizer application rates (0–300 kg N/ha (50 kg/ha unit changes)), soil type (heavy and a free-draining soil) and agroclimate location ((south and northeast of Ireland) across 16 years) on pasture growth and forage self-sufficiency using the pasture-based herd dynamic milk model merged with the Moorepark St Gilles grass growth model. The modelled outputs were grass growth, grass dry matter intake, silage harvested and offered, overall farm forage self-sufficiency and N surplus. The model outputs calculated that annual grass yield increased from 9436 kg DM/ha/year when 0 kg N/ha/year was applied to 14 996 kg DM/ha/year when 300 kg N/ha/year were applied, with an average N response of 18.4 kg DM/kg N applied (range of 9.9–27.7 kg DM/kg N applied). Systems stocked at 2.5 cows/ha and applying 250–300 kg N fertilizer/ha/year were self-sufficient for forage. As N input was reduced from 250 kg N/ha/year, farm forage self-sufficiency declined, as did farm N surplus. The results showed that a reduction in N fertilizer application of 50 kg/ha/year will require a reduction in an SR of 0.18 cows/ha to maintain self-sufficiency ( R 2 = 0.90).